Development of science interactive student worksheets oriented higher-order thinking skills for elementary school student - Baiq Niswatul Khair; Muhammad Makki; Fitri Puji Astria; Muhammad Erfan; Hasnawati Hasnawati (Jurnal Pijar Mipa, 2022)
This researchÃÂ aims to develop science interactive studentsÃ¢â¬â¢ worksheets oriented to higher-order thinking skills for the fifth elementary school students. The developed student worksheet aims to provoke and familiarize students with their higher-order thinking ability. The cognitive domain of higher-order thinking skills involved is analytical skills. The 4D development model (define, design, develop, and disseminate) was used in this study. The data in this study were collected using a validation sheet. Data analysis was carried out in a quantitative descriptive. The development results showed that science interactive students worksheets oriented to higher-order thinking skills developed were valid with an average score of 3.33. Secondly, the score for the practicality of using the science interactive studentsÃ¢â¬â¢ worksheets was 3.69 and 3.38 according to teachers and students, respectively. In conclusion, the science interactive studentsÃ¢â¬â¢ worksheets oriented towards higher-order thinking skills, are valid and practical to be used by students of the fifth-grade elementary school.